UPAYA MENINGKATKAN MOTIVASI BELAJAR, AKTIVITAS BELAJAR DAN PRESTASI BELAJAR MELALUI STRATEGI DIRECT INSTRUCTION - Nur Salim; Moh Nasuka; M. Novailul Abid (At-Tarbiyat, 2020)
This study describes the application of the direct instruction learning model in improving learning motivation, learning activities and student achievement in the moral subjects of the eighth grade MTs YAPIN Kertasemaya Indramayu. The type of research used is Classroom Action Research (CAR) or Classroom Action Research (CAR). The subjects of this study were the eighth grade students of MTs YAPIN Kertasemaya Indramayu, totaling 30 students. The instrument used to obtain preliminary data was the daily scores of students, data on student achievement was carried out objective tests carried out at the end of each cycle, and questionnaires to obtain data on learning motivation and observation to obtain data on student learning activities. The results of this study indicate there is a significant increase in each cycle. To increase student motivation, the average cycle I was 49.6%, the second cycle was 77.8% and the average cycle III was 81.3%. To increase learning activities in the first cycle by 68.9%, while the average cycle II was 77.75% and the average cycle III was 86.6%. As for the increase in learning outcomes that can be seen from the results of the classical learning completeness percentage in the first cycle by 40%, in the second cycle by 60% and in the third cycle by 80%.